A synopsis of the frullaniaceae (marchantiophyta) from colombia (2011)
Frullania (Frullaniaceae) is the second-largest liverwort genus of Colombia (after Plagiochila), with 59 recorded species in six subgenera. In this paper keys are provided for the identification of 42 Frullania species reported from Colombia together with brief descriptions of their main morphological characters, distribution, habitat and elevation in the country, as well as worldwide distribution. Some species recorded from neighbouring countries, but not yet from Colombia, are also included in the keys. The remaining species reported from Colombia are considered doubtful taxa. Frullania apollinarii Steph. is a new synonym of F. lobato-hastata Steph.